A simple synthesis technique of PWM signal - Phanphaisarn, Wasu; Saechia, Sukkharak; Koseeyaporn, Jeerasuda; Wardkein, Paramote (My University, 2006)
This article proposes a simple and accurate analytical technique for Pulse Width Modulation (PWM) harmonic spectrum whose carrier is asymmetrical ramp signal. The main concept is based on the fact that when a carrier pulse signal has much higher frequency than an information signal, period of the PWM signal is approximately constant. By considering PWM signal as a periodic signal, the one-dimensional exponential Fourier series is thus employed to be an analytical tool for mathematical analysis. The obtained analysis result in a closed form solution can therefore be utilized to easily synthesis the PWM signal. To illustrate the proposed concept, the synthesis results based on the proposed analysis are illustrated. The results show that the proposed analysis is not only a simple technique but also can provide accurate synthesis results. ©2006 IEEE.
Keywords: Pulse width modulation